Falls in hospitalized older adults and the use of fall risk-increasing drugs and anticholinergic medications in Colombia: a case‒control study - Machado-Duque, Manuel E.; Camacho-Arteaga, Lina; Sabaté, Mónica; Vidal-Guitart, Xavier; Machado-Alba, Jorge E. (Frontiers in Pharmacology, 2024)
In-hospital falls are multicausal in elderly older patientshospitalized patients. Drugs with anticholinergic load and psychotropic effects can increase the risk of falling. Objective: To determine the associations of fall risk-increasing drugs (FRIDs) and the anticholinergic risk score (ARS) with falls in hospitalized elderly aged older hospitalized patients. Methods: This was a case-control study of patients ≥65 years old of either sex treated in four clinics in Colombia between 2017 and 2020. Each patient who suffered a fall during hospitalization was matched with four hospitalized patients who did not. Sociodemographic, clinical, and pharmacological variables and the use of the ARS and FRID were evaluated. The risk associated with FRIDs was estimated using conditional logistic regression. Results: There were 250 patients and 1000 controls (ratio of 1:4), with a mean age of 77.4±7.4 years and a predominance of men (n=800; 64.0%). The majority of falls occurred during hospitalization (n=192 patients, 76.8%). Polypharmacy, calcium channel blockers, antiepileptics, antipsychotics, sodium-glucose cotransporter type 2 inhibitors, and nonsteroidal anti-inflammatory drugs were associated with falls during hospitalization. With an ARS score of 3 points, the probability of falling during the hospital stay increased (aOR: 2.34; 95% CI: 1.64-3.32). Conclusions: There is an association between suffering a fall and the use of drugs with anticholinergic load or FRIDs in hospitalized adults over 65 years of age in Colombia.